Static inter-BPEL program slicing for web services. (1st January 2012) - Mao, Chengying
Analysis and maintenance of BPEL programs play a vital role in assuring the quality of Web service software. In the paper, the concept of inter-service control flow graph (ISCFG) is proposed to represent the interaction behaviours between service units. Meanwhile, the traditional data flow analysis is extended to handle combinatorial structure of variables in BPEL program. Then, a method for constructing BPEL program dependence graph (BPDG) is addressed according to the above control and data dependence representations. Finally, a static inter-BPEL program slicing algorithm for Web service compositions is proposed, and has been validated via a real-world Web service application.